The Econometric Model of Enterprise Breakups - Anton Abdulbasah Kamil (Statistika, 2010)
we present the model that describes the process of enterprise breakups. We carried out regression analyses relating several common measures of performance to standard explanatory variables and a variable measuring the importance of the spun off unit in the master enterprise.